ホッキョクケン スバールバル ショトウ ニーオルスン ニ オケル 1997/98ネン トウキ エアロゾル カンソク - 和田, 誠; ワダ, マコト; 山形, 定; ヤマガタ, サダム; 菊地, 正; キクチ, タダシ; Wada, Makoto; Yamagata, Sadamu; Kikuchi, Tadashi (2002)
P(論文) 1997年12月15日から1998年3月日日までの期間，北極圏スパ ールパル諸島ニーオルスンにおいてエアロゾルの観測を行った．本報告では，主としてパーティクルカウンターのデータを用い、他の観測デー タを参考にして，この期間のエアロゾル個数濃度の変動を報告する．さらに北極圏航空機観測（Arctic Airborne Measurement Program 1998: AAMP 98）がスパールパル諸島周辺で行われた1998年3月8日から10日のエアロゾル，雲，降水のデー タについて，他の観測デー タの参考になるので，より詳細に報告し，エアロゾル濃度の変動の原因について考察した． Aerosol observations were carried out at Ny-Alesund, Svalbard. Arctic from December 15, 1997 to March 11, 1998. Variation of aerosol particle number in the period measured by the optical particle counter is reported in this paper. Three observational flights around Svalbard were carried out between March 8 and 10,1998. The flights were part of the Arctic Airborne Measurement Program 1998 (AAMP 98). Detailed data in the above period are also reported for supporting discussions with flight observation data. departmental bulletin paper